2020
DOI: 10.4236/as.2020.112011
|View full text |Cite
|
Sign up to set email alerts
|

Production Performance of Chicken under Farmers’ Management and Their Roles at Urban Household Economy in Southern Ethiopia

Abstract: This study was conducted to assess production performance of chicken under farmers' management and their roles in the household economy of local and exotic chickens reared at Yirgalem and Hawassa towns of Southern Ethiopia. Purposive sampling method was used for selecting the respondents. Totally, 180 respondents were selected based on their experience in chicken production. The study indicates that the average number of eggs set for incubation was 10.05 ± 0.81 of which the hatchability was 8.42 ± 1.19 eggs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…A similar observation was reported by [27] for Bovan Nera chickens when they were compared with other genotypes under an on-station management system in Nigeria. In comparison to the present findings on age at first egg under on-farm management conditions, [28], [19], [29] reported lower age at the first egg for Sasso i.e., 157.2, 176, and 177 days respectively. Likewise, Bamidele et al [20] reported the age at first egg of 120±1.3 and 133±0.6 days for Kuroiler and Sasso, respectively under on-station management, values which were also lower than those of the present study.…”
Section: Discussioncontrasting
confidence: 92%
“…A similar observation was reported by [27] for Bovan Nera chickens when they were compared with other genotypes under an on-station management system in Nigeria. In comparison to the present findings on age at first egg under on-farm management conditions, [28], [19], [29] reported lower age at the first egg for Sasso i.e., 157.2, 176, and 177 days respectively. Likewise, Bamidele et al [20] reported the age at first egg of 120±1.3 and 133±0.6 days for Kuroiler and Sasso, respectively under on-station management, values which were also lower than those of the present study.…”
Section: Discussioncontrasting
confidence: 92%
“…This indicates a higher level of interest or familiarity among respondents in hatching indigenous eggs, which could be attributed to several factors such as cultural significance, perceived higher success rates in hatching indigenous eggs, or the availability of traditional hatching methods that are better suited for indigenous eggs. In comparison, previous studies conducted in Yirgalem and Hawassa reported that the majority of respondents in those areas did not keep eggs for hatching [ 18 ]. This difference in findings between the study area and the aforementioned locations could be due to variations in cultural practices, economic factors, or specific preferences of the communities in each area.…”
Section: Resultsmentioning
confidence: 69%
“…Hatching of eggs by broody hens or flock self-propagation was the common source of poultry flock entry among farmers at the study sites. Similarly, Kejela ( 20 ) reported hatching as a major source of flock entry in local poultry production systems in Ethiopia. A study in Kogi State in Nigeria showed that purchases from the live bird market were a major source of poultry flock entry ( 21 ).…”
Section: Discussionmentioning
confidence: 99%